(untitled) - Moore, James (Hoboken, N.J., 2004)
The book carefully explores the moral questions related to pre-emptive war its effects on the future of all Americans. That includes 3 parts: Part 1: Caught by the chill; Part 2: just walk away; Part 3: Counting casualties.
Keywords: Political corruption,Iraq War, 2003-,Iraq War, 2003-,Politics and war,Chiến tranh Iraq, 2003-; Biography,Causes,Nguyên nhân; United States